Evaluate:
∫ 1 2 ∫ 1 2 ∫ 1 2 ∫ 1 2 x 1 + x 2 + x 3 + x 4 x 1 + x 2 + x 3 − x 4 d x 1 d x 2 d x 3 d x 4
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Why did the integral become 1?
Log in to reply
∫ 1 2 ∫ 1 2 ∫ 1 2 ∫ 1 2 x 1 + x 2 + x 3 + x 4 x 1 + x 2 + x 3 + x 4 d x 1 d x 2 d x 3 d x 4 = ∫ 1 2 ∫ 1 2 ∫ 1 2 ∫ 1 2 ( 1 ) d x 1 d x 2 d x 3 d x 4 = ∫ 1 2 ∫ 1 2 ∫ 1 2 x 1 ∣ 1 2 d x 2 d x 3 d x 4 = ∫ 1 2 ∫ 1 2 x 2 ∣ 1 2 d x 3 d x 4 = ∫ 1 2 x 3 ∣ 1 2 d x 4 = 1
How such a variable can be changed such a way?
Log in to reply
Since the lower bound and upper bound of each integral are all the same, you can interchange the integrals and hence, you can interchange the variables that way.
Log in to reply
Well said .Thanks
Problem Loading...
Note Loading...
Set Loading...
Let I = ∫ 1 2 ∫ 1 2 ∫ 1 2 ∫ 1 2 x 1 + x 2 + x 3 + x 4 x 1 + x 2 + x 3 − x 4 d x 1 d x 2 d x 3 d x 4
By symmetry, I is equal to:
I = ∫ 1 2 ∫ 1 2 ∫ 1 2 ∫ 1 2 x 1 + x 2 + x 3 + x 4 x 1 + x 2 − x 3 + x 4 d x 1 d x 2 d x 3 d x 4
I = ∫ 1 2 ∫ 1 2 ∫ 1 2 ∫ 1 2 x 1 + x 2 + x 3 + x 4 x 1 − x 2 + x 3 + x 4 d x 1 d x 2 d x 3 d x 4
I = ∫ 1 2 ∫ 1 2 ∫ 1 2 ∫ 1 2 x 1 + x 2 + x 3 + x 4 − x 1 + x 2 + x 3 + x 4 d x 1 d x 2 d x 3 d x 4
Adding all of these we obtain:
4 I = ∫ 1 2 ∫ 1 2 ∫ 1 2 ∫ 1 2 x 1 + x 2 + x 3 + x 4 2 x 1 + 2 x 2 + 2 x 3 + 2 x 4 d x 1 d x 2 d x 3 d x 4
4 I = 2 ∫ 1 2 ∫ 1 2 ∫ 1 2 ∫ 1 2 x 1 + x 2 + x 3 + x 4 x 1 + x 2 + x 3 + x 4 d x 1 d x 2 d x 3 d x 4
4 I = 2 ( 1 )
. . ˙ I = 2 1